The effect of applying negative pressure technique on the degree of healing of diabetic foot ulcers - الجافي, وعد; مازن حيدر ,; غانم أحمد , (Tishreen University Journal -Medical Sciences Series, 2024)
Introduction: Diabetes is considered the most common metabolic disorder around the world, and diabetic foot ulcers are one of the most important health complications associated with chronic diabetes and are the main cause of non-traumatic leg amputation. The current study aimed to evaluate the effect of applying negative pressure technology on the degree of healing of diabetic foot ulcers among patients with type 2 diabetes at Tishreen University Hospital in Lattakia .Methods According to the experimental method, the study was applied to a random sample that included 30 patients of both sexes in the vascular surgery department. They were divided into two experimental groups (15 patients) who underwent dressing changes for foot ulcers using the negative pressure technique, and control groups (15 patients) who underwent dressing changes according to the routine method approved in the hospital. The degree of healing of ulcers and the degree of ulceration were evaluated using the Risevic scale and the ulcer score scale during days (1, 5, 10, 15, 20) after the start of dressing application. Results: The results showed that there were very significant statistical differences in the degree of healing of diabetic foot ulcers in patients in the experimental group during repeated assessments compared to patients in the control group (U = 44, P = 0.004), and there were significant statistical differences in the total ulcer degree)X2،10.09= p(0.018= compared to patients in the control group. Conclusions: The negative pressure technique has a role in improving the healing of diabetic foot ulcers. Therefore, the study recommends the necessity of adopting it as a routine dressing method for diabetic foot ulcer patients and conducting more research on it in order to improve the healing of patients and reduce the need for lower limb amputation.